Pre-auction lane selection in an integrated production–distribution planning problem. Issue 11 (2nd November 2021) - Triki, Chefi; Piya, Sujan; Fu, Liang-Liang
ABSTRACT: Integrating production scheduling with transportation decisions is an important problem that is receiving increasing interest from the logistics industry. As an order is received, the manufacturer starts planning its production while considering the appropriate decisions for delivery. The company can adopt an auction paradigm to involve external occasional drivers, besides using its own fleet for the delivery. Ahead of an auctioning process, the company should decide which deliveries should be served by its fleet and which can be assigned to the occasional drivers. This is known as the shipper lane selection problem (SLSP). This article integrates the SLSP with production scheduling and proposes an integer formulation and heuristic methods to solve the resulting integrated problem (I-SLSPS). Experiments show the validity of the proposed methods and their capability in achieving minimum cost for the integrated problem.